Evidence for Bone Marrow Adult Stem Cell Plasticity: Properties, Molecular Mechanisms, Negative Aspects, and Clinical Applications of Hematopoietic and Mesenchymal Stem Cells Transdifferentiation - Ivana Catacchio; Simona Berardi; Antonia Reale; Annunziata De Luisi; Vito Racanelli; Angelo Vacca; Roberto Ria (Stem Cells International)
In contrast to the pluripotent embryonic stem cells (ESCs) which are able to give rise to all cell types of the body, mammalian adult stem cells (ASCs) appeared to be more limited in their differentiation potential and to be committed to their tissue of origin. Recently, surprising new findings have contradicted central dogmas of commitment of ASCs by showing their plasticity to differentiate across tissue lineage boundaries, irrespective of classical germ layer designations. The present paper supports the plasticity of the bone marrow stem cells (BMSCs), bringing the most striking and the latest evidences of the transdifferentiation properties of the bone marrow hematopoietic and mesenchymal stem cells (BMHSCs, and BMMSCs), the two BM populations of ASCs better characterized. In addition, we report the possible mechanisms that may explain these events, outlining the clinical importance of these phenomena and the relative problems.